Practical embedded controllers design and troubleshooting with the Motorolla [i.e. Motorola] 68HC11 - Park, John. (Practical professional books from Elsevier., 2003)
This book will help the technician, engineer and user understand the microcontroller-based systems along with the most common problems and their solutions. This book covers design, specification, programming, installation, configuration and of course troubleshooting. An engineer's guide to the design, applications and troubleshooting of microcontroller-based systems The introductory chapters on embedded microcontroller architecture and programming are written at the right level with an applications focus for practicing engineers A highly topical book with a wide readership involved with product design and industrial processes including control systems.